PENGEMBANGAN MODUL PEMBELAJARAN KONSTRUKSI POLA BUSANA DI JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - KARMILA, IIN; Ernawati, Ernawati; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aims to produce a medium of learning in the form of modules that can facilitate students in learning Construction Patterns Clothing. This study is also to gain an overview of the feasibility of the module as a learning medium Clothing Pattern Construction. This study is a Research and Development (Research and Development (R & D) is the research methods used to produce a particular product, and test the effectiveness of a particular product. This module in tested in the Department of Family Welfare to students D3 dressmaking with the number 38. The stages are carried out in the development of this module are: 1) recognize potential problems. 2) gather information, 3) develop product design, 4) the results of the development phase, In the result of this development stage of data analysis are: 1) the validity of the data analysis, 2) data analysis practicalities, and the effectiveness of data analysis. Based on the data analysis of the results showed that the validity of the test is done to the validator that expert learning media and materials experts are, 4.07 can be considered valid, the practicalities of trials conducted to students is 3.38% can be categorized as practical while the effectiveness of data analysis of student activities in the lecture increased from 59% to 81% which can be categorized effectively. This module is located in a very decent criteria are used as a medium of learning in terms of the validity of the data analysis, the practicalities and effectiveness.